DC-SIGN Expression in Intestinal Epithelial Cells Regulates Sepsis-Associated Acute Intestinal Injury Via Activating ERK1/2-NF-κB/P65 Signaling. Issue 4 (October 2019) - Chen, Weiwei; Ma, Li; Li, Ranran; Huang, Shunwei; Xie, Rongli; Chen, Ying; Zhao, Bing; Fei, Jian; Qu, Hongping; Chen, Hao; Mao, Enqiang; Chen, Er-zhen
ABSTRACT: Objective: The aim of the study was to investigate the role of dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN) in intestinal epithelial cells (IECs) in regulating sepsis-induced acute intestinal injury and systemic inflammatory response. Methods: To induce sepsis condition, Male C57BL/6 mice were exposed to cecal ligation and puncture (CLP) in vivo, whereas a normal human IECs line (FHs74Int) was stimulated with lipopolysaccharide (LPS) in vitro . DC-SIGN siRNA pretreatment was used to knock down DC-SIGN expression both in vivo and in vitro . The expression of DC-SIGN was detected by western blot and immunohistochemistry. The expression of total and phosphorylation of ERK1/2 and NF-κB/p65 was examined by western blot. The levels of cytokines in serum and culture supernatant were measured by ELISA. The survival rate and organ injures of septic mice were also assessed. Results: In vivo, DC-SIGN expression in mouse IECs was time-dependently upregulated by CLP. CLP-induced phosphorylation of ERK1/2 and NF-κB/p65 was effectively inhibited by DC-SIGN siRNA pretreatment, leading to the decrease of systemic inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-10, and IFN-γ), which alleviated multiple organ injuries and increased the survival rate of septic mice. In vitro, DC-SIGN expression in FHs74Int was significantly upregulated by LPS stimulation in a time- and dose-dependent manner. DC-SIGN knockdown abolished LPS-induced ERK1/2 and NF-κB/p65 phosphorylation, resulting in the decrease of cytokines release by FHs74Int. Conclusions: Sepsis-induced DC-SIGN expression in IECs plays a significant role in regulating acute intestinal injury and systemic inflammatory response. The inhibition of DC-SIGN exhibited protective effects on sepsis-associated organ injury and systemic inflammation.